2023
DOI: 10.3390/medicina59061031
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Tunnel Geometry and Graft Inclination Angles in Anterior Cruciate Ligament Reconstruction Using a Flexible Reamer System

Abstract: Background and Objectives: The aim of this study is to investigate the femoral tunnel geometry (femoral tunsnel location, femoral graft bending angle, and femoral tunnel length) on three-dimensional (3D) computed tomography (CT) and graft inclination on magnetic resonance imaging (MRI) after anatomic anterior cruciate ligament (ACL) reconstruction using a flexible reamer system. Materials and Methods: A total of 60 patients who underwent anatomical ACL reconstruction (ACLR) using a flexible reamer system were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Some authors reported that femoral tunnel placement on 3D-CT can influence graft inclination and maturation on MRI. Lee et al [45] reported that a total of 60 patients who underwent anatomical ACL reconstruction using flexible reamer system showed femoral tunnel located at 24.1 ± 5.9% in high to low direction and at mean 29.7 ± 4.4% in deep to shallow direction on postoperative 3D-CT. They aimed to target the femoral tunnel position slightly toward the AM bundle rather than the center of the entire bundle and received 3D-CT feedback after each procedure.…”
Section: Clinical Relevance Of Postoperative 3d Ctmentioning
confidence: 99%
“…Some authors reported that femoral tunnel placement on 3D-CT can influence graft inclination and maturation on MRI. Lee et al [45] reported that a total of 60 patients who underwent anatomical ACL reconstruction using flexible reamer system showed femoral tunnel located at 24.1 ± 5.9% in high to low direction and at mean 29.7 ± 4.4% in deep to shallow direction on postoperative 3D-CT. They aimed to target the femoral tunnel position slightly toward the AM bundle rather than the center of the entire bundle and received 3D-CT feedback after each procedure.…”
Section: Clinical Relevance Of Postoperative 3d Ctmentioning
confidence: 99%